Fatores associados à atividade física na deficiência visual - Lima Scherer, Roger (Educación Física y Ciencia.)
The aim is to verify the determining factors for the practice of regular physical activity in leisure in adults with visual impairment in Greater Florianópolis. A pre-structured and validated interview was applied in 168 visually impaired adults, members of one Association for Integration of the Blind. The results show that 44 percent are in the range recommended for BMI and 30 percent considered active, unlike these individuals in childhood, when 63 percent of them were considered active. In the analysis of odds ratios, it was found that adults with active behavior in childhood have a lower chance of being active in adult life, and those who have completed full or post-graduate education and were moderately active in childhood are more likely to be active than other adults with visual impairment. These results show a significant increase in sedentary lifestyle, overweight and obesity in this population segment, increasing the chances of developing chronic noncommunicable diseases.